High-efficient single-phase, non-isolated, multi-input microinverter with common ground for photovoltaic systems - Alhasi, Anees; Luk, Patrick Chi-Kwong; Ibrahim, Khalifa Aliyu; Luo, Zhenhua (Elsevier, 2025)
Single-phase non-isolated microinverters used in photovoltaic (PV) systems commonly encounter two persistent challenges: High-frequency leakage current and fluctuating power delivery. This paper presents a novel single-phase, non-isolated multi-input microinverter topology with a common-ground structure that effectively eliminates ground leakage current without requiring additional active components. The proposed microinverter architecture integrates a dual-boost configuration and uses only four active switches. This is especially advantageous in terms of the component count, which is beneficial to enhance reliability, reduce cost, and simplify the overall system design. With one, two, or four PV inputs, it can operate without interruption under unbalanced voltage or partial shading and even if some inputs drop to zero. A tailored modulation scheme minimizes conduction losses while maintaining a stable direct-current (DC)-link voltage, and a decoupling capacitor efficiently absorbs the single-phase pulsating power, thus overcoming one major limitation in existing microinverter designs. By validating with a 1-kW GaN-based prototype, both the simulated and experimental results demonstrate its high efficiency, robustness, and practical suitability for cost-effective PV applications, with a peak efficiency value of 94.8%.
Keywords: 40 Engineering; 4008 Electrical Engineering; 4009 Electronics, Sensors and Digital Hardware; 7 Affordable and Clean Energy; Dual-boost; Leakage current elimination; Multiple input microinverter; Non-isolated; Photovoltaic; Single-boost